43.0k views
1 vote
Which expression is equivalent to 486 – 9 + 6 + 33 × 2?

User Samiq
by
4.9k points

2 Answers

4 votes

Answer:

404

Explanation:

P-parenthesis

E-exponents

M-multiplication

D-division

A-addition

S-subtraction

486-9+6+33*2

486-9+6+66

486-81=404

User Tivoni
by
5.3k points
4 votes

Answer:

549

Explanation:

Remember PEMDAS (this is the order of operations).

P = Parentheses

E = Exponents

M = Multiplication

D = Division

A = Addition

S = Subtraction

So, lets do multiplication first.

33*2 = 66

So, our new expression is 486 - 9 + 6 + 66.

Remember that addition and subtraction are reversible.

486 - 9 = 477

477 + 6 = 483

483 + 66 = 549

User Naqeeb
by
5.3k points